PENGARUH IKLIM ORGANISASI TERHADAPKINERJAORGANISASI DI SD NEGERI SE-KECAMATAN KEBUMEN, KABUPATEN KEBUMEN - Ruftikawati, Yuliana (2016)
This thesis titled "The Influenced Of Organizational Climate To Organizational Performance In National Primary School as at KebumenSubdistrict Of KebumenRegency ". the study was done because the urgensity of the primary school as basic education, and included compulsory education citizens of the republic of Indonesia, which needs to be known the implementation. The research questions include: 1) how is the organizational climate in National Primary School as at KebumenSubdistrict Of Kebumen Regency?, 2) how the description of the organizational performance In National Primary School As At KebumenSubdistrict Of Kebumen Regency?. And 3) how big the influence of the organizational cliate to organizational performance in National Primary School As At KebumenSubdistrict Of Kebumen Regency?. The type of this research is quantitative descriptive research, where the depiction of the data obtained is really actual and presented in numbers. The subject of this research is the educators and staff of National Primary School as at KebumenSubdistrict Of Kebumen Regency. The object of this research is the organizational climate and organizational performance (school), which research tools is the closed questionnaire. The research result obtain that, the first, the climatic condition in National Primary School as at KebumenSubdistrict Of Kebumen Regency categorized very well, and the performance of the organization category either. Second, the organizational climateconditions greatly affect the performance of the organization. Third, although the academic achievement of students found affordable, yet closer to the non-academic achievement National Primary School as at KebumenSubdistrictOfKebumen Regency is still low.;--- Skripsi ini berjudul "Pengaruh Iklim Organisasi Terhadap Kinerja Organisasi Di SD Negeri Se- Kecamatan Kebumen, Kabupaten Kebumen". Penelitian ini dilakukan karena urgensitas jenjang pendidikan Sekolah Dasar sebagai pendidikan dasar dan termasuk program wajib belajar Warga Negara Republik Indonesia, yang mana perlu diketahui penyelenggaraannya. Pertanyaan penelitian dalam penelitian ini diantaranya: 1) Bagaimana kondisi iklim organisasi di SD Negeri Se-KecamatanKebumen, KabupatenKebumen?, 2) Bagaimanagambarankinerjaorganisasi di SD Negeri Se-KecamatanKebumen, KabupatenKebumen?, dan 3) Seberapabesarpengaruhiklimorganisasiterhadapkinerjaorganisasi di SD Negeri Se-KecamatanKebumen, KabupatenKebumen?. Jenispenelitianiniadalahpenelitiandeskriptifkuantitatif, dimanapenggambaran data-data yang diperoleh benar-benar aktual dan disajikan dalam bentuk angka-angka sebagai hasil penelitian yang dilakukan terhadap sampel penelitian.Subjek penelitian ini adalah tenaga pendidikdan kependidikan SD Negeri Se-Kecamatan Kebumen, Kabupaten Kebumen, sedangobjekpenelitiannyaadalahiklimorganisasidankinerjaorganisasi (sekolah), dengan alat penelitian berupa kuesioner tertutup. Hasil penelitian diperoleh bahwa, pertama, kondisiiklimorganisasi di SD Negeri Se-KecamatanKebumenberkategorisangatbaik, dankinerjaorganisasinyaberkategoribaik. Kedua, kondisiiklimorganisasisangatmempengaruhikinerjaorganisasi.Ketiga,meskiprestasiakademiksiswaditemukanbernilaibaik, namuncapaianprestasi non-akademik di SD Negeri se-Kecamatan Kebumen masih rendah